Advancements in employing two-dimensional nanomaterials for enhancing skin wound healing: a review of current practice - Jiaqi Zhao; Tianjiao Li; Yajuan Yue; Xina Li; Zhongjian Xie; Han Zhang; Xing Tian (Journal of Nanobiotechnology, 2024)
Abstract The two-dimensional nanomaterials are characterized by their ultra-thin structure, diverse chemical functional groups, and remarkable anisotropic properties. Since its discovery in 2004, graphene has attracted significant scientific interest due to its potential applications in various fields, including electronics, energy systems, and biomedicine. In medicine, graphene is used for designing smart drug delivery systems, especially for antibiotics, and biosensing. Skin trauma is a prevalent dermatological condition that increasingly contributes to morbidities and mortalities, thus representing a significant health burden. During tissue damage, rapid skin repair is crucial to prevent blood loss and infection. Therefore, drugs used for skin trauma must possess antimicrobial and anti-inflammatory properties. Two-dimensional (2D) nanomaterials possess remarkable physical, chemical, optical, and biological characteristics due to their uniform shape, increased surface area, and surface charge. Graphene and its derivatives, transition-metal dichalcogenides (TMDs), black phosphorous (BP), hexagonal boron nitride (h-BN), MXene, and metal-organic frameworks (MOFs) are among the commonly used 2D nanomaterials. Moreover, they exhibit antibacterial and anti-inflammatory properties. This review presents a comprehensive discussion of the clinical approaches employed for wound healing treatment and explores the applications of commonly used 2D nanomaterials to enhance wound healing outcomes.